2003
DOI: 10.1021/jf0211433
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Resistance to Helicoverpa zea in Tobacco Expressing an Activated Form of Maize Ribosome- Inactivating Protein

Abstract: Progeny of two transgenic tobacco (Nicotiana tabacum L.) lines that expressed an activated form of maize (Zea mays L.) ribosome-inactivating protein (RIP) had varying resistance to the insect species tested. A subset of R(2) plants from the two lines appeared to be more resistant to larvae of the cigarette beetle, Lasioderma serricorne (F.), and the tobacco hornworm, Manduca sexta (L.) than the wild type plants. Progeny (R(3)) of the more resistant R(2) plants were tested more extensively for insect resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 22 publications
2
42
0
Order By: Relevance
“…Ten newly hatched larvae were added to each dish. The degree of feeding was determined by visually counting the number of 0.25 and 1.0 mm 2 holes or equivalent daily (Dowd and Lagrimini 1997, Dowd et al 2003, 2007a. Larval mortality was also determined daily during the 2-day assays.…”
Section: Bioassaysmentioning
confidence: 99%
“…Ten newly hatched larvae were added to each dish. The degree of feeding was determined by visually counting the number of 0.25 and 1.0 mm 2 holes or equivalent daily (Dowd and Lagrimini 1997, Dowd et al 2003, 2007a. Larval mortality was also determined daily during the 2-day assays.…”
Section: Bioassaysmentioning
confidence: 99%
“…Insecticidal activity of type-2 RIPs has been demonstrated towards some insects (Gatehouse et al 1990;Dowd et al 1998Dowd et al , 2003Wei et al 2004). Although the enzymatic mechanism of RIP activity is well defined, the physiological steps by which ribosome inactivation leads to cell death are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Dowd et al (2006) have shown significant feeding reduction and larval mortality in two Lepidopteran species (Helicoverpa zea and Trichoplusia ni) by feeding on transgenic tobacco plants expressing maize RIP. In previous studies, these authors also reported significant mortality caused by maize RIP in the beetles Lasioderma serricorne and Carpophilus freemani (Dowd et al, 1998(Dowd et al, , 2003. RIPs from seeds of dicot plants, such as castor bean (Ricinus communis), soapwort (Saponaria officinalis) and bitter gourd (Momordica cochinchinensis), were shown to be toxic toward beetles but not caterpillars (Gatehouse et al, 1990).…”
Section: Discussionmentioning
confidence: 85%
“…In these in planta experiments, beet armyworm caterpillars were strongly affected in their survival, whereas aphids were affected less with sublethal effects on progeny and population build up (ShahidiNoghabi et al, 2008). It has been reported before by Dowd et al (2003) that the entomotoxicity of the maize RIP to Helicoverpa and Lasioderma is higher in a leaf assay with transgenic tobacco overexpressing the maize RIP than in a bioassay where insects were fed on an artificial diet dosed with maize RIP.…”
Section: Toxicity Of Elderberry Rip Lectin In Insectsmentioning
confidence: 84%